2016
DOI: 10.1021/acs.nanolett.6b03860
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Smooth Self-Assembled Monolayer for High-Mobility Organic Field-Effect Transistors

Abstract: Despite the need for molecularly smooth self-assembled monolayers (SAMs) on silicon dioxide surfaces (the most common dielectric surface), current techniques are limited to nonideal silane grafting. Here, we show unique bioinspired zwitterionic molecules forming a molecularly smooth and uniformly thin SAM in "water" in <1 min on various dielectric surfaces, which enables a dip-coating process that is essential for organic electronics to become reality. This monomolecular layer leads to high mobility of organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…The mussel‐inspired phenolic (or catecholic) polymer binders are used for surface modification of silicon nanoparticles in high‐performance lithium‐ion batteries . The phenolic zwitterionic surfactants are used on nano‐grooved dielectric substrates as surface modifiers to produce organic field‐effect transistors . In our previous research, a single‐surface primer containing phenolic and acrylic groups enabled adherence to silica fillers that enhanced the toughness of the composite consisting of filler and polymer resin by interfacial bridging to the acrylic resin…”
Section: Introductionmentioning
confidence: 99%
“…The mussel‐inspired phenolic (or catecholic) polymer binders are used for surface modification of silicon nanoparticles in high‐performance lithium‐ion batteries . The phenolic zwitterionic surfactants are used on nano‐grooved dielectric substrates as surface modifiers to produce organic field‐effect transistors . In our previous research, a single‐surface primer containing phenolic and acrylic groups enabled adherence to silica fillers that enhanced the toughness of the composite consisting of filler and polymer resin by interfacial bridging to the acrylic resin…”
Section: Introductionmentioning
confidence: 99%
“…The most common primers for mineral fillers in load-bearing polymer composites, such as those used in dental restorative applications, rely on silane-based chemistries. However, silane grafting involves uses of toxic chemicals [1,2] and difficult processing [3,4] and therefore there is a great demand for alternative strategies for surface priming.…”
mentioning
confidence: 99%
“…[5] Inspired by the natural DOPA chemistry, numerous laboratories have exploited catechol functionalization in the translation of this bioadhesion to synthetic systems [1012] and for various applications [1,1315] such as functional materials; for example, catechol-functionalized polymers were used as binders for silicon lithium battery anodes, [15] and catecholic zwitterionic surfactants were employed as surface modifiers on nanogrooved dielectric substrates for organic field-effect transistors. [1] Although previous studies using catechol-decorated polymers have demonstrated improvements in adhesion, [5,12,16] the performance of such manmade polymers, [16] as well as isolated native mussel and engineered proteins [17] is still far lower than that of whole natural mussel plaques, in terms of the total energy required to dislodge a plaque from a surface. [18] These differences may arise from the lack of consideration given in previous work to the heterogeneous nature of the mussel plaque structures [19] and their impact on load transfer within the material.…”
mentioning
confidence: 99%
See 2 more Smart Citations